Exploration of differentially expressed mRNAs and miRNAs for pediatric acute myeloid leukemia - Wang, Qing; Yue, Chao; Liu, Qin; Che, Xuchun (Frontiers in Genetics, 2022)
Background: To establish a comprehensive differential gene profile for pediatric acute myeloid leukemia patients (pAML) based on two independent databases and verify the differentially expressed genes using in vitro and in vivo analyses. Methods: The mRNA and miRNA sequencing information of GSE2191 and GSE35320, clinically recruited pAML individuals, and human AML cell line (NB4 cells) were utilized in the study. Results: Compared with the control sample, pAML patients demonstrated a total of 778 differentially expressed genes, including 565 upregulated genes and 213 downregulated genes. The genes including ZC3H15, BCLAF1, PPIG, DNTTIP2, SRSF11, KTN1, UBE3A, PRPF40A, TMED5, and GNL2 were the top 10 potential hub genes. At the same time, 12 miRNAs demonstrated remarkable differential expressions in pAML individuals compared with control individuals, as five upregulated and seven downregulated miRNAs. The hsa-miR-133, hsa-miR-181, and hsa-miR-195 were significantly downregulated. Building a miRNA–mRNA regulatory network, hsa-miR-133 regulated ZC3H15, BCLAF1, SRSF11, KTN1, PRPF40A, and GNL2. Using the NB4 cell model, hsa-miR-133 treatment inhibited cell proliferation capacity, which could be attenuated by a single mRNA transfection or a combination of ZC3H15 and BCLAF1. At the same time, hsa-miR-133 mimic treatment could significantly accelerate cell apoptosis in NB4 cells, which was also ZC3H15- and BCLAF1-dependent. The concentrations of ZC3H15 and BCLAF1 were investigated in peripheral blood using the ELISA method for the clinical control and pAML samples. In pAML samples, the expression levels of ZC3H15 and BCLAF1 were significantly enhanced (p < 0.01), regardless of the classification. Conclusion: Collectively, this study hypothesized several promising candidates for pAML formation.